Design and evaluation of a sustainable solar based combined cycle for multi-output generation in UAE - Alkhadar, Hamda Ali (2023)
A Master of Science thesis in Mechanical Engineering by Hamda Ali Alkhadar entitled, “Design and evaluation of a sustainable solar based combined cycle for multi-output generation in UAE”, submitted in April 2023. Thesis advisor is Dr. Mohammad O. Hamdan and thesis co-advisor is Dr. Sameer Al-Asheh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).